Unlighted Maceration and Ultrasound Technique: The Key to Gaining Stable Trans-Resveratrol from Alternative Sources in Tempeh and Soybean Seed Coat - Irnidayanti, Y.; Sutiono, Dias Rima (Pakistan Journal of Nutrition, 2019)
Backgorund and Objective: The aim of this study was to determine the best extraction conditions to gain stable trans-resveratrol from tempeh and soybean seed coat. Materials and Methods: The first stage was to determine trans-resveratrol of tempeh and soybean seed coat during extractions at room temperature, with a mechanical maceration speed up to 180 rpm for 2 h and sonication for 5 min. This method consisted of an orderly extraction with a rotary evaporator at a boiling point of 60°C, rotation of 100 rpm under a vacuum of 556 mBar with an efficiency of 80%, an evaporation enthalpy of 513 J g–1 and a density of 784 kg m–1 3, followed by N-hexane extraction at a boiling point of 60°C, rotation of 100 rpm under a vacuum of 335 mBar with an efficiency of 80%, an evaporation enthalpy of 368 J g–1 and a density of 660 kg m–1 3 in three cycles for 2 h and 55 min. In this work, the extraction method utilized sonication and maceration under dark conditions. Results: Results indicated that acetone is the optimal solvent with a concentration of 70% and a solvent/material ratio of 10/1 (v/w), an extraction time of 175 min, a mechanical maceration of 120 min and sonication for 5 min at 40 kHz at 100 W and 38°C. Trans-resveratrol was obtained and observed by TLC and HPLC. Conclusion: These methods signi cantly a ected the stability of trans-resveratrol. The best results used acetone as the solvent with sonication-assisted unlighted maceration extraction.